SOCIAL MEDIA–A REAL SOURCE OF PROLIFERATION OF INTERNATIONAL TERRORISM - MARCU, Mihaela; BĂLTEANU, Cristina (Annales Universitatis Apulensis Series Oeconomica, 2014)
Although in 2011 there were registered the fewest terrorist attacks since 2007, the groups involved in such acts significantly expanded geographically, this being due to the use of modern technologies and, implicitly, the use of social networks. Thus, the terrorist organizations have developed quickly by using at larger scale new methods of communication and information, these giving them the ability to communicate over long distances and in a safe way. In this context, this paper had as the main objective the analysis of the role and the implications of social media in the proliferation of terrorism. The results of the study showed an increased presence of extremist groups in the virtual world of the Internet, 9 of 10 cases of organized terrorism on the Internet being based on social media.